A critical investigation of telecentre provision and utilization by rural women : with special reference to Botlokwa Youth Telecentre - Madima, Ntombintombi Mabel (University of Limpopo ( Turfloop campus), 2007)
There is gross uneven access and utilization of Information and Communication Technology (ICT) between developed and underdeveloped communities in South Africa. As a result the majority of the underdeveloped communities which are mainly found in rural areas fail to participate in the global ICT arena. Rural communities’ especially rural women are subjected to deprivation, poverty and isolation. Government sought to reverse the situation through the provision of Telecentres and Multi-purpose Community Centres (MPCCs). To understand the plight of the rural women, different theories ranging from capitalism to socialism were reviewed in an attempt to trace the mode of South African production which caused the problem and some understanding of the solution possible. The theory of oppression by Paul Freire (1970) serves as the main point of focus on how rural women fail to utilize Telecentres and MPCCs. Qualitative and quantitative approaches were adopted in order to present the perceptual views of these women. Various methods of collecting data were used in order to have a wider perspective of how Telecentres and MPCCs are utilized by rural women. This includes a profound investigation through which a pilot study, participant observation, focus group, interviews and questionnaires became instrumental to the whole research. The findings of the pilot study conducted in Mogalakwena Hewlett Packard inclusive of community (HPi-community) reflected that there are discrepancies and deficiencies which exit between Mogalakwena HPi-community and the three Telecentres Botlokwa, Mankweng and Mohodi. The tripartite marriage between Government Hewlett Packard and the municipality enable the Mogalakwena HPi-community to provide better ICT facilities. The other three Telecentres fail to meet the standard of the Mogalakwena HPi- community due to the fact that they lack financial support. Participant observation assisted in discovering that ICT access created a good relationship between Botlokwa Telecentre and its neighbouring institutions. It was also discovered that most youths come for computer-skill acquisition. Focus groups interviews were conducted using English and the local language (Sepedi) in order to meet the rural women’s level of understanding. Through in depth analysis, the study indicates that poverty, unemployment, limited funding, illiteracy, and unavailability of ICT facilities for the disabled are the main issues that contribute to the low impact of Telecentre and MPCC utilization. Apart from this analysis, ICT access has a significant impact on the lives of rural communities especially women. However, there is still a need for an accelerated growth in ICT utilization. It is recommended that effective mechanisms be put in place to assist improve the situation in ICT provision. This must involve the people themselves taking initiatives, of course with the active support of government.
Thesis (M.A.(Media studies ))--University of Limpopo, 2007
Keywords: Telecentre; Rural women; 384.968; Information technology - South Africa - Limpopo; Women in development - South Africa - Limpopo